2019
DOI: 10.1017/neu.2019.43
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal prenatal psychological stressors and distress with maternal and early infant faecal bacterial profile

Abstract: Objective:Findings from animal studies indicate that the early gut bacteriome is a potential mechanism linking maternal prenatal stress with health trajectories in offspring. However, clinical studies are scarce and the associations of maternal psychological profiles with the early infant faecal bacteriome are unknown. This study aimed to investigate the associations of prenatal stressors and distress with early infant faecal bacterial profiles in a South African birth cohort study.Methods:Associations between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 68 publications
1
31
0
Order By: Relevance
“…Other observations derived from our analysis should be considered in the context of the neurodevelopmental hypothesis of SCZ, namely the decreased relative abundance of Intestinibacter and Weisella in SCZ compared to HC. Both sets of finding appear at odds with the observations of increased levels of Intestinibacter in children with neurodevelopmental disorders, including autism [ 45 ], a disorder that shares some clinical features of SCZ, and of Weisella in infants born to mothers exposed to interpersonal violence compared to those with no/low exposure [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other observations derived from our analysis should be considered in the context of the neurodevelopmental hypothesis of SCZ, namely the decreased relative abundance of Intestinibacter and Weisella in SCZ compared to HC. Both sets of finding appear at odds with the observations of increased levels of Intestinibacter in children with neurodevelopmental disorders, including autism [ 45 ], a disorder that shares some clinical features of SCZ, and of Weisella in infants born to mothers exposed to interpersonal violence compared to those with no/low exposure [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of geographic area differences in gut microbial composition (50), the conduct of the Dawe et al and Slykerman et al RCTs in the same country (of New Zealand) may ensure a level of homogeneity in baseline gut microbial composition. However, these trials enrolled women with a different ethnicity and socioeconomic profiles, and likely, with dissimilar underlying risk for poor mental health (51) and dysbiosis of pregnancy gut microbiota (52). It is noteworthy then, that despite potential differences in the psychosocial and gut microbial profile of study women across the two RCTs, a benefit was found for a lactobacillus probiotic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to the complex association between gut microbiome and depression, there is also evidence that antimicrobials used to treat depression can result in gut dysbiosis through antimicrobial effects (Ting-Ting [ 62 , 63 ]). Another Firmicutes genus that was significantly associated with depressive symptom scores, Weissella , was previously identified in infants born to mothers exposed to psychological stressors and distress such as intimate partner violence [ 64 ]. Nevertheless, the source of these depression-associated genera in the gut and the exact mechanisms of how they affect or are affected by brain functions and behavior require further study.…”
Section: Discussionmentioning
confidence: 99%